Buru Island and Political Detainees in the Memory of Indonesian Literature: A New Historicist Study of Amba by Laksmi Pamuntjak - Wiyatmi, Wiyatmi (Humanities Diliman: A Philippine Journal of Humanities, 2021)
In Indonesia’s sociopolitical context, Buru Island is one of the areas often associated with political detainees. Buru Island is also the setting of several Indonesian novels that highlight political detainees’ stories, notably Amba (2012) by Laksmi Pamuntjak. This paper aims to describe the locus of Buru Island, Indonesia, as one of the places for political detainees during the country’s New Order era and afterward, and as depicted in a number of Indonesian literary works, particularly in Pamuntjak’s Amba, by using the perspective of new historicism. Through this study, it is hoped that the significance of Buru Island for many people and particularly the relatives of political detainees and fighters for human rights yearning for justice could be brought to light and better understood. As one of the literary works retelling the life of the political detainees on Buru Island, Amba can be considered as a novel endeavoring to reopen the collective memory of the Indonesian people to the mystery surrounding the event of the Movement of September 30, 1965 and the exile of political detainees from Java to the Island.
Keywords: Buru Island, political detainees, Amba, Indonesian Communist Party, collective memory